The prophet between doctrine, literature and arts: historical legacies and their unfolding - Gril, Denis 19XX-; Reichmuth, Stefan; Sarmis, Dilek ca. 20./21. Jh. (The presence of the prophet in early modern and contemporary Islam, 2021)
This first collective volume outlines his figure in the early Islamic tradition, and its later transformations until recent times that were shaped by Prophet-centered piety and politics. A variety of case studies offers a unique overview of the interplay of Sunnī amd Shīʿī doctrines with literature and arts in the formation of his image. They trace the integrative and conflictual qualities of a “Prophetic culture”, in which the Prophet of Islam continues his presence among the Muslim believers.